Fashioning the Canadian landscape : essays on travel writing, tourism, and national identity in the pre-automobile era - Little, J. I. (John Irvine), 1947- (University of Toronto Press, 2018)
In his book Fashioning the Canadian Landscape, J.I. Little examines how Canada, much like the United States, came to be identified with its natural landscape. Little argues that in contrast to America, Canada's image was strongly influenced by the picturesque convention favoured by British travel writers.